Immigration and changes in the epidemiology of hemoglobin disorders in Italy : an emerging public health burden - Cataldo Francesco (BMC, 2012)
Abstract Background In the last years Italy is confronting with massive migratory movements from developing countries where hemoglobinopathies are widespread. This is causing a large diffusion and a changing spectrum in the epidemiology of hemoglobin disorders in Italy. Methods Investigations recently published in Italy on hemoglobinopathies among immigrants were revised in order to appreciate the impact of immigration from developing countries on epidemiology of these pathologies and to outline adequate guidelines of prevention. Results Although in Italy there is a limited number of investigations regarding the relation between immigration and hemoglobin disorders, published data show that in our Nation there is a changing and increasing spectrum of hemoglobinopathies linked to immigration. Conclusions Prospective and retrospective actions of public healthy preventive policy are requested, based upon information (health educational programs for immigrants and caregivers), screenings among immigrants (school screening, pre-marital, preconception and early pregnancy screening, newborn screening), counseling for foreign at-risk couples and healthy carriers.